Laboratory Diagnosis of Genital Tuberculosis: A Narrative Review (Bangladesh Journal of Infectious Diseases, 2023)
Genital tuberculosis is a leading cause of infertility in high tuberculosis burden countries like Bangladesh. Diagnosing this condition can be challenging due to the diverse ways it can present, which requires a physician to have a high level of suspicion. The fallopian tubes are mainly affected, and the endometrium in 50% of cases1. Diagnostic modalities usually include histopathology, microscopy, solid and liquid culture tests, Polymerase Chain Reaction (PCR) tests, immunohistochemistry tests, radiology imaging and laparoscopic and hysteroscopic procedures.Bangladesh Journal of Infectious Diseases, December 2023;10(2):92-100